'Still too much socialism in Britain': The legacy of Margaret Thatcher. Issue 3 (May 2014) - Beynon, Huw
Abstract Margaret Thatcher's death in 2013 was followed by extensive tributes to her achievements, often describing her role in 'saving Britain'. Other more sceptical voices pointed to the destructive aspects of her politics. This article explores these issues through an examination of the major confrontation with the coal miners and their trade union the NUM. Through published sources and interviews with key actors it argues that the dispute epitomised Mrs Thatcher's concern to weaken trade unionism and defeat socialism. This (rather than issues of employment or energy policy) is seen as her strategic objective and her success can be measured in the changed nature of the Labour Party. In this the exercise of state power was decisive. However, the article questions the extent to which 'Thatcherism' and the associated individualism has prevailed as an hegemonic force. It provides examples of a continuing patterns of collective behaviour and beliefs and raises the possibility of an emerging and different form of labour movement.